基于MATLAB的行走机构设计及仿真软件的开发 - 程秀芳; 高瑞香 (Jixie chuandong)
In visual and simulated environment,the type of a walking mechanism of walking robots based on function bionics is studied.According to the rule of optimization design,the walking mechanism is designed based on anklebone track of human.Movement analysis and motion simulation of the mechanism are accomplished.The result proved that it is an ideal mechanism of walking robot.